PENGAYAAN PEMAHAMAN HADIS SABAR UNTUK GURU-GURU PESANTREN MODERN NURUL HUDA- CIKARAGEMAN- SETU- BEKASI - Khairil Ikhsan Siregar; Sa'dullah (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
AbstractThe partnership with Pesantren Modern Nurul Huda Cikaregenan Setu-Bekasi was agreed upon by the lecturers of the Islamic Education Department as the site for community service four years ago. The Faculty of Social Science at Universitas Negeri Jakarta facilitated the funding so that the Community Service Program runs smoothly. The current training topic revolves around understanding the content of the hadith on patience in the context of a teacher's character as part of our community service. The methods employed during the training include lectures, discussions, and enrichment material, such as enriching the content of the hadith on patience and applying thematic hadith analysis techniques. Furthering the study of patient hadith is essential and greatly pertains to the background of teachers/educators appointed by Mitra, who are participants in this community service training. As a result, the understanding of the teachers improves with the following cycle: a significant change occurs before and after the training. It is still necessary to share knowledge and experiences to understand the hadiths and become familiar with the method of syarh/explanation of the hadith. For instance, to assess whether training has improved the participants' understanding, a comparison was made. Before the training, 13% had a complete understanding, 57% had some understanding, and 30% had little understanding. After participating, 30% had a complete understanding, 65% had some understanding, and 13% had little understanding. This training aimed to motivate teachers to continuously understand the Hadiths by providing enrichment and discussing in-depth the patient Hadiths and steps to study themed Hadith.AbstrakPada kegiatan pengabdian kepada masyarakat bersama mitra Pesatren Modern Nurul Huda Cikaregenan Setu- Bekasi sebagaimana yang disepakati dari dosen-dosen Prodi Pendidikan Agama Islam menjadikannya tempat binaan Pengabdian Kepada Masyarakat Fakultas sejak empat tahun lalu. Dan Fakultas Ilmu Sosial Universitas Negeri Jakarta yang menjadi fasilitator pengadaan dana sehingga kegiatan Pengabdian kepada Masyarakat (P2M) berjalan lancar. Tema pelatihan yang diusung pada pengabdian kepada masyarakat pada kali ini memahami matan (isi) hadis sabar, konteksnya dengan karakter pendidik. Metode yang digunakan dalam pelatihan ceramah dan diskusi dan materi pengayaan diantaranya: pengayaan materi hadis sabar, pengayaan materi metode kajian hadis tematik. Pengayaan kajian memahami hadis-hadis sabar penting dan berhubungan sekali dengan latar belakan guru-guru/pendidik yang ditunjuk Mitra sebagai peserta dalam pelatihan pengabdian kepada masyarakat ini. masih perlu berbagi pengalaman ilmu dalam upaya memahami hadis dan mengenal metode syarh/penjelasan hadis. Maka hasilnya pemahaman guru-guru meningkat dengan gambaran siklus berikut: perubahan signifikan dari sebelum mengikuti pelatihan dan setelahnya. Misalnya untuk kuis apakah pelatihan telah menambah pemahaman peserta, dengan perbandingan, sebelumnya paham sekali 13 % , paham 57%, kurang paham 30%, dan setelah mengikuti, paham sekali 30%, paham 65 %, dan kurang paham 13%. Melalui pelatihan ini dengan memberikan pengayaan dan diskusi pendalaman materi hadis sabar dan langkah-langkah kajian hadis tematik diharapkan guru-guru semakin termotivasi memahami hadis- hadis secara berkelanjutan.